P043 Infection with citrullinating porphyromonas gingivalis can induce autoimmunity to human ribosomal proteins. (March 2019) - Jenning, M; Marklein, B; Konthur, Z; Nonhoff, U; Burmester, G-R; Skriner, K
Abstract : Career situation of first and presenting author: Young investigator. Introduction: Porphyromonas gingivalis (P g.) is involved in triggering self-reactive immune responses when citrullinating bacterial or human proteins. However, first evidence to link anti-ribosomal T and B cells responses to rheumatoid arthritis (RA) has been published but the mechanism is still not clear. 1 Infection based autoimmunity induced by citrullination of human proteins with P g. peptidyl arginine deiminase from RA patient (RA-PPAD) and crossreactivity binding induced by P g. was investigated using affinity purified RA patient antibodies and a monoclonal antibodies to cit-RA-PPAD. Objectives: Antibodies to RA-PPAD isolated from an RA patients (RA-PPAD) was first time linked to target specific citrullinated ribosomal proteins. Methods: Screening of RA sera was conducted on 37.830 unique human proteins on protein marcoarrays (http://www.engine-gmbh.de) with 30 RA sera. The autoantibody response to 840 different proteins was recorded and bioinformatically evaluated. Protein arrays were citrullinated with PAD2, 4, rabbit PAD and RA-PPAD. Sera and affinity purified antibodies were used to detect reactivity to 840 autoantigens. Results: A human protein macroarray consisting of 840 indentified autoantigens from RA patients was modified by human PAD2 and PAD4, rabbit PAD, and RA-PPAD form P g..Using cit specific monoclonal antibodies we identified the ribosomal proteins (RP), RPL18a, RPS27a, modified by PAD2, RPL18a and MRPS11 modifies by Pad4, and RPL7L1 modified by rabbit PAD specifically targeted. In addition 6 RA patient sera and 3 osteoarthritis (OA) control sera were used to identify the citrullinated RA-PPAD specific modified autoantigens not targeted when modified by human PAD2 or PAD4 or rabbit Pad. We identified the RA-PPAD citrullinated ribosomal Proteins RPL3, RPL21, RPS24, RPL9, RPL15, RPS24.RPS3a, MRPL28 specifically targeted by RA patients. This identifies ribosomal proteins as major specific RA-PPAD citrullination targets. Moreover, affinity purified antibodies bound to native and citrullinated RA-PPAD from 6 RA patient sera and 3 OA patient sera were tested for crossreactvity on citrullinated human proteinarray. Antibodies to citrullinated ribosomal proteins MRPS11, RPL21, RPS3a, RPL18a, RPS27a, MRPL28 were detected in the RA group but not in the OA control group. Conclusions: Failure of Porphyromonas gingivalis clearance in RA patients leads to infection induced enzymatic mimicry based autoreactivity targeting evolutionary conserved human ribosomal proteins. Autoimmunity to ubiquitous self-antigens may trigger localized tissue damage in RA. Reference: Ito Y, et al . Detection of T cell responses to a ubiquitous cellular protein in autoimmune disease. Science 2014;346:363–368. Disclosure of Interest: None declared.